STUDI TENTANG KINERJA KEPALA SEKOLAH MENENGAH ATAS SWATA DI KECAMATAN SUKADIRI: PERSEPSI GURU DAN PEGAWAI - Sundusiah, Siti; Khusaini, Khusaini; Suherman, Agus (JIPIS, 2021)
This study aims to examine the effect of leadership, personal abilities, and school culture on the performance of school principals. The data used in this study are primary data obtained from questionnaires distributed to teachers in private high schools in Sukadiri district. This study had a population of 200 teachers and a sample of 67 teachers. The analytical method used a multiple regression analysis. The results showed that leadership, personal abilities, and school culture had a positive and significant effect on the performance of high school principals. It meant that the leadership, personal skills, and school culture would result in a good performance. The implication of the research results is that a good principal's performance must be supported by the creation of good leadership, abilities, and school culture. Principals are expected to encourage school programs that are directed at improving the achievement of a leadership model that is accepted by all school members. In addition, the principal can encourage all school members to create an academic culture at school.